(-a-5b+5)5ab=

Simple and best practice solution for (-a-5b+5)5ab= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-a-5b+5)5ab= equation:


Simplifying
(-1a + -5b + 5) * 5ab = 0

Reorder the terms:
(5 + -1a + -5b) * 5ab = 0

Reorder the terms for easier multiplication:
5ab(5 + -1a + -5b) = 0
(5 * 5ab + -1a * 5ab + -5b * 5ab) = 0

Reorder the terms:
(25ab + -25ab2 + -5a2b) = 0
(25ab + -25ab2 + -5a2b) = 0

Solving
25ab + -25ab2 + -5a2b = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), '5ab'.
5ab(5 + -5b + -1a) = 0

Ignore the factor 5.

Subproblem 1

Set the factor 'ab' equal to zero and attempt to solve: Simplifying ab = 0 Solving ab = 0 Move all terms containing a to the left, all other terms to the right. Simplifying ab = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(5 + -5b + -1a)' equal to zero and attempt to solve: Simplifying 5 + -5b + -1a = 0 Reorder the terms: 5 + -1a + -5b = 0 Solving 5 + -1a + -5b = 0 Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -1a + -5 + -5b = 0 + -5 Reorder the terms: 5 + -5 + -1a + -5b = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1a + -5b = 0 + -5 -1a + -5b = 0 + -5 Combine like terms: 0 + -5 = -5 -1a + -5b = -5 Add '5b' to each side of the equation. -1a + -5b + 5b = -5 + 5b Combine like terms: -5b + 5b = 0 -1a + 0 = -5 + 5b -1a = -5 + 5b Divide each side by '-1'. a = 5 + -5b Simplifying a = 5 + -5b

Solution

a = {5 + -5b}

See similar equations:

| ln(x-4)+(x+1)=ln(x-8) | | -5+5b=60 | | Sin(x)=.76 | | 5=a-4 | | -171=19r | | 60=-4x | | 3x^2+6x=297 | | 2y-5x-10=0 | | 6.5/3x+5=6 | | 6n-32=n^2-6n+3 | | U+2.87=6.56 | | 7(x-1)=12 | | 3n-32=n^2-6n+3 | | m+4+8m=-23 | | 16+n=30 | | -(a-4)=1 | | -y^2+4y-1=0 | | 8(4r+5+9s)= | | -8y+5=-6 | | 4-9X=3-10X-(7-X) | | 4(a-3)+a=15+2a+9 | | 3y+8=65 | | Y=-7lnx | | 2x-7=6x+3 | | 2(-3-1)+(2y+7)= | | 1/3(9x+3/4)-5=2/3(12x+6) | | 4x-14=-1 | | 8y=-4x+42 | | 98x^2=72 | | f(x)=4x^2+15 | | x^3=7x-2 | | .4w^10+9m^2=0 |

Equations solver categories